Evaluation Of The CIPP Model Of School Football Development Early Children In Karanganyar District - Ihsan Badaruddin; Agus Kristiyanto; Hanik Liskustyawati (Cita Konsultindo Research Center, 2023)
The activity aims to find out the evaluation of the cipp model of school football development early children in karanganyar district. This research was conducted in karanganyar regency which is located at field 413 kodim palur karanganyar, dprd field kab. Karanganyar, koripan village field and lalung village field. The samples in this study were 70 people consisting of 23 administrators, 7 trainers, 40 athletes.in this study, researchers will use the cipp model evaluation because the cipp model is an evaluation model that is carried out in a complex manner which includes: context evaluation, input evaluation, process evaluation, product evaluation. This research on the evaluation of the early childhood football school development program in karanganyar regency (CIPP model program evaluation) obtained results in the form of interesting facts about the problems that existed in a coaching program that was implemented. There are many positive and negative findings that have been obtained by researchers during research at early childhood football schools in karanganyar district, these findings include: 1) The early childhood football school in karanganyar regency has a coaching program that is already running even though it is not as expected. 2) The facilities and infrastructure at the karanganyar regency early childhood football school are still inadequate and the standards are not met. 3) Funding problems that are still not optimally fulfilled. 4) The coaching program process still has many problems